Changes in Surface Potential of Activated Carbon Due to Adsorption of Ions - Badri, M.; Crouse, Karen Anne (1989)
The construction of a carbon electrode and the measurement of the changes in the potential that developed on its surface as a result of adsorption of ions are discussed as a function of the cation adsorption and ionization of the functional groups on the surface of carbon.